2020
DOI: 10.3389/fnut.2020.00119
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Trial in the Efficacy of Yokukansankachimpihange on REM Sleep Behavior Disorder in Dementia With Lewy Bodies

Abstract: Background: Clonazepam (CNZP) is effective in ∼90% of patients with rapid eye movement sleep behavior disorder (RBD) but has risks of oversedation, muscular relaxation, and adverse effects on cognitive function when used to treat RBD associated with dementia with Lewy bodies (DLB). Yokukansankachimpihange (YKSCH), a traditional herbal medicine, decreases sleep latency and increases sleep stage 2, like benzodiazepines (BZPs), but does not cause adverse events such as oversedation, muscular relaxation, and adver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…In addition to the included RCTs, all other studies (Iwasaki et al, 2005;Shinno et al, 2007;Xu et al, 2007;Shinno et al, 2008;Hayashi et al, 2010;Kawanabe et al, 2010;Guo et al, 2011b;Iwasaki et al, 2012;Nagata et al, 2012;Yang et al, 2012;Sumiyoshi et al, 2013;Kudoh et al, 2016;Ohsawa et al, 2017;Meguro and Yamaguchi, 2018;Xu, 2018;Manabe, 2020) have reported that HM improved BPSD in at least one indicator.…”
Section: Results From Other Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to the included RCTs, all other studies (Iwasaki et al, 2005;Shinno et al, 2007;Xu et al, 2007;Shinno et al, 2008;Hayashi et al, 2010;Kawanabe et al, 2010;Guo et al, 2011b;Iwasaki et al, 2012;Nagata et al, 2012;Yang et al, 2012;Sumiyoshi et al, 2013;Kudoh et al, 2016;Ohsawa et al, 2017;Meguro and Yamaguchi, 2018;Xu, 2018;Manabe, 2020) have reported that HM improved BPSD in at least one indicator.…”
Section: Results From Other Included Studiesmentioning
confidence: 99%
“…Thirty-four studies ( Chen et al, 1997 ; Chen et al, 2013 ; Chen, 2020 ; Du et al, 2015 ; Fang et al, 2018 ; Gu et al, 2018 ; Guo et al, 2011a ; Han, 2018 ; Hu et al, 2015 ; Huang and Xu, 2019 ; Li, 2020 ; Li et al, 2018 ; Lin et al, 2016 ; Liu et al, 2015 ; Motohashi, 2006 ; Pan et al, 2014 ; Pu et al, 2014 ; Shen, 2013 ; Shen et al, 2019 ; Shen et al, 2018 ; Shi et al, 2020 ; Yao et al, 2014 ; Zhang et al, 2015a ; Zhang et al, 2018 ; Zhang, 2012 ; Zhou, 2018 ; Zhou, 2015 ; Zhou and Wei, 2015 ; Zhu et al, 2019 ; Zuo, 2017 ; Xu, 2018 ; Guo et al, 2011b ; Xu et al, 2007 ; Yang et al, 2012 ) were published in China, and 18 studies ( Furukawa et al, 2017 ; Mizukami et al, 2009 ; Monji et al, 2009 ; Okahara et al, 2010 ; Teranishi et al, 2013 ; Terasawa et al, 1997 ; Kudoh et al, 2016 ; Meguro and Yamaguchi, 2018 ; Hayashi et al, 2010 ; Iwasaki et al, 2012 ; Iwasaki et al, 2005 ; Kawanabe et al, 2010 ; Manabe, 2020 ; Nagata et al, 2012 ; Ohsawa et al, 2017 ; Shinno et al, 2008 ; Sumiyoshi et al, 2013 ; Shinno et al, 2007 ) were published in Japan. The type of dementia was Alzheimer’s disease, vascular dementia, two or more types of dementia, and dementia with Lewy bodies in 26 ( Chen, 2020 ; Fang et al, 2018 ; Furukawa et al, 2017 ; ...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations